(3GdeNJUQ aj GdYQhVs - (3GHf GdSbGW , CHh YHO Gddgs
(3ChdgG (B:s
(3jHJOF HGdHGH GdChd Hbhdg (B( (3EYde Cf GdTYQ JJLGPHI Ydhe CQHYI , hgj Yde GdChRGf hYde GdbhGai hYde GdHdGZI hYde GdfbO s
(3BNQgG (B:s
(3hbO GfJgi GdcdGe ai GdUOQ adfTQY ai TQM GdeNJUQ HMhd Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B6s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdYQhV hGdbhGais